Past, Present, and Future of the Scaling Relations of Galaxies and Active Galactic Nuclei - D’Onofrio, Mauro; Marziani, Paola; Chiosi, Cesare (Frontiers in Astronomy and Space Sciences, 2021)
We review the properties of the established Scaling Relations (SRs) of galaxies and active galactic nuclei (AGN), focusing on their origin and expected evolution back in time, providing a short history of the most important progresses obtained up to now and discussing the possible future studies. We also try to connect the observed SRs with the physical mechanisms behind them, examining to what extent current models reproduce the observational data. The emerging picture clarifies the complexity intrinsic to the galaxy formation and evolution process as well as the basic uncertainties still affecting our knowledge of the AGN phenomenon. At the same time, however, it suggests that the detailed analysis of the SRs can profitably contribute to our understanding of galaxies and AGN.